Marketing research - Cooper, Donald R.; Schindler, Pamela S. (McGraw-Hill/Irwin, 2006)
Takes the approach that each student needs an overview first in order to appreciate the nuances and details of the specific techniques they will be asked to employ to develop high quality information. The first part of this book presents the overview, while parts 2, 3, and 4 provide the details on methodologies and techniques.